SOEP-IS 2016.2 - BIOBIRTH: Birth biography of female and male respondents - DIW Berlin / SOEP (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The file BIOBIRTH covers the following information: (1) sum, year of birth and sex of the biological children of a male/female respondent up to the last date of interview (2) Person identifier (KIDPNR(n)) of the children (provided the child can be identified) which corresponds to variable PID in file PPFAD. BIOBIRTH is based on every male/female respondent who has ever had at least one successful SOEP or IS interview. For each of these respondents, the data set BIOBIRTH documents the birth biography with one row per respondent in the dataset. The annual update focuses on including information on new births collected in the individual questionnaire or in the biographical questionnaire. Furthermore respondents who have been interviewed for the first time but who gave no information on births yet are included. The latter are either new household members or teenagers who have reached the required minimum for a SOEP-IS participation (16 years). For that reason BIOBIRTH can be described as an accumulative data set, in which the entire birth biography of all SOEP-IS respondents is presented.
Keywords: 330